2020
DOI: 10.4103/jpbs.jpbs_47_20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and management of general dentist toward medication-related osteonecrosis of the jaws

Abstract: A BSTRACT Background: Medication-related osteonecrosis of the jaw (MRONJ) is an intense negative drug response causing increasing bone destruction in the maxillofacial area of patients. Aims and Objectives: To evaluate the knowledge and attitude of dental practitioner regarding risk factors of MRONJ in Saudi Arabia. Materials and Methods: A cross-sectional, questionnaire survey was carried out in King Khalid Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Al-Maweri et al (2020), Miranda-Silva et al (2020), andBruckmoser et al (2021) have also shown that specialists and more trained and specialized professionals showed better knowledge when compared to general dentists about the subject. Taken together, these results reinforce the need for continous education about bisphosphonates and BAONJ for both dental students and dentists (Al-Eid et al, 2020;Alqhtani et al, 2020;Almousa et al, 2021;Ozkan et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Al-Maweri et al (2020), Miranda-Silva et al (2020), andBruckmoser et al (2021) have also shown that specialists and more trained and specialized professionals showed better knowledge when compared to general dentists about the subject. Taken together, these results reinforce the need for continous education about bisphosphonates and BAONJ for both dental students and dentists (Al-Eid et al, 2020;Alqhtani et al, 2020;Almousa et al, 2021;Ozkan et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
“…The present sample was composed mainly by dental students and participants derived from private dental schools, in contrast to the sample studied by De Lima et al (2015). Some studies have included only dental students (Escobedo et al, 2017;Rosella et al, 2017), while others have included only graduated dental professionals (Alhussain et al, 2015;Vinitzky-Brener et al, 2017;Hristamyan-Cilev et al, 2019;Al-Eid et al, 2020;Al-Maweri et al, 2020;Alqhtani et al, 2020;Arnaud et al, 2021;Ozkan et al, 2021). More recently, Franchi et al (2020) have showed the results derived from a sample of medical students and Miranda-Silva et al ( 2020) compared the results derived from dentists, physicians and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in Saudi revealed that 60% of the dentists had poor knowledge regarding BRONJ with weak positive correlation with work experience. 16 Comparably, in a similar study conducted in Saudi, only 61% dentists were aware of the term osteonecrosis of jaw and 35% of the candidates were able to diagnose it correctly. Whereas less than 60% knew about radiations causing the disease.…”
Section: Discussionmentioning
confidence: 82%
“…In 2003, it was first accepted that bisphosphonate-related osteonecrosis of the jaw is a side effect for patients who are using intravenous bisphosphonates as treatment of malignant diseases with bone metastases [ 9 ]. The duration and type of treatment, as well as medical anamnesis, could affect the risks for the patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches from dentists around the whole world reveal that most of these participants have inadequate knowledge about MRONJ as an adverse effect of these drugs [ 10 , 13 , 16 20 ]. Awareness and knowledge about MRONJ are essential for all dentists to diagnose “at at risk” patients for suitable consultation and management [ 17 ].…”
Section: Introductionmentioning
confidence: 99%